2019
DOI: 10.1002/pon.5163
|View full text |Cite
|
Sign up to set email alerts
|

Losing a parent to cancer as a teenager: Family cohesion in childhood, teenage, and young adulthood as perceived by bereaved and non‐bereaved youths

Abstract: Objective The aim of this study was to investigate levels of perceived family cohesion during childhood, teenage years, and young adulthood in cancer‐bereaved youths compared with non‐bereaved peers. Methods In this nationwide, population‐based study, 622 (73%) young adults (aged 18‐26) who had lost a parent to cancer 6 to 9 years previously, when they were teenagers (aged 13–16), and 330 (78%) non‐bereaved peers from a matched random sample answered a study‐specific questionnaire. Associations were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 40 publications
(50 reference statements)
0
20
1
Order By: Relevance
“…Although there is a shortage of studies following siblings over time, research indicates that child functioning is closely associated with—and often dependent on—parent and family functioning 8,9 . For example, poor cohesiveness or having difficulty expressing feelings and emotions in the family unit can predict posttraumatic stress reactions in children 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a shortage of studies following siblings over time, research indicates that child functioning is closely associated with—and often dependent on—parent and family functioning 8,9 . For example, poor cohesiveness or having difficulty expressing feelings and emotions in the family unit can predict posttraumatic stress reactions in children 10 …”
Section: Introductionmentioning
confidence: 99%
“…8,9 For example, poor cohesiveness or having difficulty expressing feelings and emotions in the family unit can predict posttraumatic stress reactions in children. 10 Parents play a significant role in providing support throughout a child's development-whether the child is ill or healthy-but parents of children with cancer are at risk of own marked or prolonged distress or psychopathology. 11 Parents experience multiple stressors throughout the illness trajectory, including managing treatment and side effects, financial strain, a sense of being dependent on the care provided, and balancing care of healthy siblings.…”
mentioning
confidence: 99%
“…Bereavement in children and adolescents has been shown to be associated with increased risk of suicide attempts [ 8 , 9 ] and increased mortality [ 10 , 11 ], and previous research based on the same study sample as the current study showed almost a doubled risk of self-injury in the first 6–9 years following teenage bereavement [ 12 , 13 ]. While not all bereaved children and adolescents will face these negative outcomes of bereavement [ 14 , 15 ], risk factors such as sudden, unexpected or traumatic [ 5 ] loss, parental depression [ 16 ] and poor family cohesion [ 17 , 18 ] have been identified. Complicated or prolonged grief is another factor that has been shown to be associated with those negative health-related outcomes in bereaved children and adolescents [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, low family cohesion and conflict between parents increased the risk of depression and anxiety in family members ( Park et al, 2018 ; Cano et al, 2020 ). In families with a high degree of cohesion, individuals can get more psychological help and emotional support within the family ( Birgisdóttir et al, 2019 ), so that the psychological pressure can be appropriately relieved. Positive emotional expression within the family can prevent suppression of inner feelings and buffer internal conflicts, especially in the face of stressful events.…”
Section: Discussionmentioning
confidence: 99%